Continued increase in the prevalence of asthma and atopy. Issue 1 (1st January 2001) - Downs, S H; Marks, G B; Sporik, R; Belosouva, E G; Car, N G; Peat, J K
Abstract : AIMS: To describe the change in the prevalence of wheeze, diagnosed asthma, and atopy in Wagga Wagga, NSW, Australia, between 1992 and 1997, and to compare this to the increase in prevalence reported between 1982 and 1992. METHODS: A cross sectional study of the prevalence of respiratory symptoms and atopy in schoolchildren aged 8–11 years (n = 1016, response rate 71%) in 1997 compared with studies of similar design in 1992 (response rate 83%, n = 850) and 1982 (response rate 88%, n = 769). Main outcome measures were respiratory symptoms measured by parent completed questionnaire and atopy measured by skin prick tests. RESULTS: Between 1992 and 1997, the prevalence of wheeze increased by 5.1% (95% CI 1.2 to 9.0), asthma diagnosis by 8.1% (95% CI 3.8 to 12.4), and atopy by 6.7% (95% CI 2.2 to 11.2). Similar increases in prevalence had been found between 1982 and 1992. CONCLUSIONS: The prevalence of wheeze, asthma diagnosis, and atopy in Wagga Wagga has continued to increase.